Adaptive Orthogonal Gradient Algorithm Based on Fair Cost Function - Suchada Sitjongsataporn; Theerayod Wiangtong (My University, 2024)
This paper presents an adaptive orthogonal gradient algorithm with the unconstrained Fair cost function. An adaptive orthogonal gradient-based algorithm is investigated with the help of orthogonal projection mechanism to update the approximate tap-weight vector for the convergence enhancement. Fair cost function is preferable with a smooth points that is able to detect the statistical characteristics of error. Objective of this work is to present an adaptive orthogonal gradient algorithm using Fair cost function (OGA-Fair) to enhance the performance. Simulation results show that proposed adaptive OGA-Fair algorithm can perform with the fast convergence rate and robustness better than the existing method.
Keywords: Advanced Adaptive Filtering Techniques; Image and Signal Denoising Methods; Blind Source Separation Techniques